Hard to “tune in”: neural mechanisms of live face-to-face interaction with high-functioning autistic spectrum disorder - Tanabe, Hiroki C.; Kosaka, Hirotaka; Saito, Daisuke N.; Koike, Takahiko; Hayashi, Masamichi J.; Izuma, Keise; Komeda, Hidetsugu; Ishitobi, Makoto; Omori, Masao; Munesue, Toshio; Okazawa, Hidehiko; Wada, Yuji; et al. (Frontiers in Human Neuroscience, 2012)
Individuals with autism spectrum disorders (ASD) are known to have difficulty with eye contact. This might make it difficult for partners to communicate with them face-to-face. To elucidate the neural substrates of live inter-subject interactions of ASD patients and typically-developed (normal) subjects, we conducted hyper-scanning functional MRI with 21 subjects with autistic spectrum disorder (ASD) paired with normal subjects, and with 19 pairs of normal subjects as a control. Baseline eye contact was maintained while subjects performed a real-time joint-attention task. The task-related effects were modeled out, and inter-individual correlation analysis was performed on the residual time-course data. ASD–Normal pairs were less accurate at detecting gaze direction than Normal–Normal pairs. Performance was impaired both in ASD subjects and in their normal partners. The left occipital pole activation caused by gaze processing was reduced in ASD subjects, suggesting that deterioration of eye-cue detection in ASD is related to impairment of early visual processing of gaze. By contrast, their normal partners showed greater activity in the bilateral occipital cortex and the right prefrontal area, indicating a compensatory workload. Inter-brain coherence in the right IFG reported previously in Normal–Normal pairs during eye contact was diminished in ASD–Normal pairs. Intra-brain functional connectivity between the right IFG and right superior temporal sulcus (STS) in normal subjects paired with ASD subjects was reduced compared with in Normal–Normal pairs. This functional connectivity was positively correlated with performance of normal partners in eye-cue detection. Considering the integrative role of the right STS in gaze processing, inter-subject synchronization during eye contact might be a prerequisite for eye-cue detection by the normal partner.